2020
DOI: 10.1111/jocn.15270
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ socialisation to emotion management during early clinical placement experiences: A qualitative study

Abstract: Aims and objectives To explore nursing students’ subjective experience of emotions during first‐year clinical placements, strategies used to manage their emotions and socialisation to emotion management. Background Emotion regulation is a key source of stress for early career and student nurses. Clinical placement experiences can elicit strong emotions in nursing students; however, they may be unprepared for the challenge of regulating their emotions in real‐world practice. How nursing students learn to manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 46 publications
2
42
0
7
Order By: Relevance
“…Conversely, a lack of role models may foster unsafe clinical practices (Killam et al., 2013) and feelings of being an outsider (Jonsén et al., 2013; Kern et al., 2014). Our findings support the concept of belonging as a need influencing the students’ learning, motivation and confidence (Grobecker, 2016; McCloughen et al., 2020). In addition, the findings indicate that the supplementary simulation training may have enhanced students´ ability to handle experiences of limited supervision and feelings of being alone at the nursing homes by adding to their sense of social integration.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Conversely, a lack of role models may foster unsafe clinical practices (Killam et al., 2013) and feelings of being an outsider (Jonsén et al., 2013; Kern et al., 2014). Our findings support the concept of belonging as a need influencing the students’ learning, motivation and confidence (Grobecker, 2016; McCloughen et al., 2020). In addition, the findings indicate that the supplementary simulation training may have enhanced students´ ability to handle experiences of limited supervision and feelings of being alone at the nursing homes by adding to their sense of social integration.…”
Section: Discussionsupporting
confidence: 84%
“…The feeling of competence is a sense of confidence and effectiveness in one’s action, not an attained skill or capability (Deci & Ryan, 2002). When students are introduced to difficult and demanding tasks or asked challenging questions, supervisors need to recognise students’ need to feel competent and to provide appropriate support and feedback (Arkan et al., 2018; McCloughen et al., 2020; Niemiec & Ryan, 2009). The students in the current study reported that the simulation training was crucial for them to develop knowledge and confidence in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of included studies are presented in Table 1. The studies examined all levels of course seniority: novice students (year 1, n = 6 studies) (Alshahrani et al, 2018;Cooper et al, 2015;Jonsén et al, 2013;McCloughen et al, 2020;Moquin et al, 2018;Thomas et al, 2015); second-year (Arkan et al, 2018) and third-or fourth-year students (n = 7 studies) (Bawadi et al, 2019;Birks et al, 2017;Ching et al, 2020;Jarvelainen et al, 2018;Kern et al, 2014;Lopez et al, 2018;van Der Riet et al, 2018). Some examined dual and multiple year groups (Brynildsen et al, 2014;Courtney-Pratt et al, 2018;George et al, 2020;Walker et al, 2014), or the year was not specified (Hurley et al, 2020;Jack et al, 2018;Jamshidi et al, 2016;Lea et al, 2015;MacDonald et al, 2016;Miller-Rosser et al, 2019;O'Mara et al, 2014;van Giersbergen et al, 2016;Vatansever & Akansel, 2016).…”
Section: Results/findingsmentioning
confidence: 99%
“…In units with a low staffing ratio, there may be no supervisor for a student, particularly affecting a beginner student who would need direction ( Arkan et al, 2018 ; McCloughen et al, 2020 ). There may be a lack of sequence practice to skill level with students expected to carry out nursing duties beyond their scope of practice ( Arkan et al, 2018 ; Lopez et al, 2018 ), undermining their confidence.…”
Section: Results/findingsmentioning
confidence: 99%
“…Since responsibility for curriculum has subsequently been devolved to the individual nations of the UK, it remains compulsory only in England (and even there, only in schools whose funding arrangements require them to follow the National Curriculum). Over the last thirty years, a number of other organisations have been established to support teaching and learning about the Holocaust in the UK, such as the Anne Frank Trust (1991), the the concept to fields as diverse as nursing (McCloughen et al, 2020), journalism (Knight, 2020), careers education (Olry-Louis, 2018) and librarianship (Jan and Anwar, 2018). Bodenheimer and Shuster (2020: 63) are among those who have advocated that the teaching profession should be included, since in their opinion it is one that 'requires employees to engage in emotional labour' -a view which corresponds with Olson et al's (2019: 130) previous assertion that 'teaching is imbued with emotions', as well as Kitching's (2009: 144) belief that 'the desire to teach [is] intrinsically emotional'.…”
Section: Introductionmentioning
confidence: 99%